MORPHOLOGICAL AND MORPHOPHONEMIC PROCESS OF ALAY VARIATION - Dwi Astuti Wahyu Nurhayati (Center of Language and Cultural Studies, 2015)
This study reports the morphological and morphonemic process of Alay variation as a communication model among Indonesia youth. Data were analysed by using qualitative approach applying thematic framing. Data were obtained from facebook and online writing communication. The study reveals that morphological process of Alay Words consist of affixation and non-affixation. Affixation includes: Internal change, Infixation, and Core of vowel change. Non-Affixation includes: Borrowing, Coinage, Clipping, Acronym, Multiple process, Reduplication, and Combination Text. Morphophonemic process is categorized into Loss of Phonemes, Addition of Phonemes, and Simple Consonant Change. This way, Indonesia youth use this variety to code and mix among their group for internet account. Alay indicates an alternative in compressing words under 160 character-limit in text messages, ignoring standard rules as method of making strong password for internet discourse and expression of mood and feeling dealing intimate mood, such as: love, heart break, and relationship.